Characteristics of high‐latitude precursor flows ahead of dipolarization fronts. Issue 5 (22nd May 2017) - Li, Jia‐Zheng; Zhou, Xu‐Zhi; Runov, Andrei; Angelopoulos, Vassilis; Liu, Jiang; Pan, Dong‐Xiao; Zong, Qiu‐Gang
Abstract: Dipolarization fronts (DFs), earthward propagating structures in the magnetotail current sheet characterized by sharp enhancements of northward magnetic field, are capable of converting electromagnetic energy into particle kinetic energy. The ions previously accelerated and reflected at the DFs can contribute to plasma flows ahead of the fronts, which have been identified as DF precursor flows in both the near‐equatorial plasma sheet and far from it, near the plasma sheet boundary. Using observations from the THEMIS (Time History of Events and Macroscale Interactions during Substorms) spacecraft, we show that the earthward particle and energy flux enhancements ahead of DFs are statistically larger farther away from the neutral sheet (at high latitudes) than in the near‐equatorial region. High‐latitude particle and energy fluxes on the DF dawnside are found to be significantly greater than those on the duskside, which is opposite to the dawn‐dusk asymmetries previously found near the equatorial region. Using forward and backward tracing test‐particle simulations, we then explain and reproduce the observed latitude‐dependent characteristics of DF precursor flows, providing a better understanding of ion dynamics associated with dipolarization fronts. Key Points: Ions reflected from dipolarization fronts (DFs) contribute to the high‐latitude DF precursor flows near the plasma sheet boundary layer High‐latitude ion fluxes on DF dawnside are greater than those on duskside, which is opposite to the dawn‐dusk asymmetries near the equator The reversed dawn‐dusk asymmetry is caused by the nature of ion DF reflection and by ion dawnward accumulation in the ambient plasma sheet